Fun with Algorithms 7th International Conference, FUN 2014, Lipari Island, Sicily, Italy, July 1-3, 2014, Proceedings - Ferro, Alfredo; Luccio, Fabrizio; Widmayer, Peter (Theoretical Computer Science and General Issues, 2014)
This book constitutes the refereed proceedings of the 7th International Conference, FUN 2014, held in July 2014 in Lipari Island, Sicily, Italy. The 29 revised full papers were carefully reviewed and selected from 49 submissions. They feature a large variety of topics in the field of the use, design and analysis of algorithms and data structures, focusing on results that provide amusing, witty but nonetheless original and scientifically profound contributions to the area. In particular, algorithmic questions rooted in biology, cryptography, game theory, graphs, the internet, robotics and mobility, combinatorics, geometry, stringology, as well as space-conscious, randomized, parallel, distributed algorithms and their visualization are addressed.